2017
DOI: 10.7567/apex.10.052201
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature self-powered energy photodetector based on optically induced Seebeck effect in Cd3As2

Abstract: We demonstrate an intrinsically fast, Seebeck-type metal-semimetal-metal infrared photodetector based on Cd 3 As 2 crystals. The Seebeck voltage is induced under off-center illumination, leading to asymmetric temperature gradients and net current flow.The sensor's room-temperature responsivity is 0.27 mA/W. The photocurrent signal is readily registered at a modulation frequency of 6 kHz, and the sensor's intrinsic bandwidth is predicted to approach terahertz. We find that the photocurrent depends on the optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…[219][220][221][222][223][224] In this context, first steps have been made to create ultra-fast broadband photo-detectors as well as mid-infrared optical switches based on Cd 3 As 2 . [225][226][227] Cd 3 As 2 hosts all necessary promising properties that already make graphene an attractive photosensitive material, while it offers the further huge advantage that it interacts with light way better due to its 3D nature. Photodetectors based on a Au-Cd 3 As 2 -Au architecture exhibit an ultrafast photocurrent response of 6.9 ps, which is one order of magnitude faster than commercially available state-of-the-art systems.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…[219][220][221][222][223][224] In this context, first steps have been made to create ultra-fast broadband photo-detectors as well as mid-infrared optical switches based on Cd 3 As 2 . [225][226][227] Cd 3 As 2 hosts all necessary promising properties that already make graphene an attractive photosensitive material, while it offers the further huge advantage that it interacts with light way better due to its 3D nature. Photodetectors based on a Au-Cd 3 As 2 -Au architecture exhibit an ultrafast photocurrent response of 6.9 ps, which is one order of magnitude faster than commercially available state-of-the-art systems.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…In addition, the intriguing properties of high carrier mobility and linear dispersion of band energy make Cd 3 As 2 a potential candidate for optoelectronic applications in high-speed, broadband photodetectors, mid-infrared optical switches and modulators. 4,[23][24][25][26][27][28] Optical excitation with circularly-polarized light can induce a spin-polarized charge current due to the angular momentum selection rule, known as the circular photogalvanic effect (CPGE), while excitation with linearly-polarized light can generate a spin-unpolarized charge current, known as the linear photogalvanic effect (LPGE). 29,30 CPGE, as an optically-excited spin orientation transport effect, has been widely used to investigate the spin polarization nature in a variety of semiconductors, and to reveal their fundamental spin-orbit coupling physics and potential opto-spintronic device applications.…”
Section: Introductionmentioning
confidence: 99%
“…It reveals properties of the hot electrons important in high-field devices. More directly, it can guide optoelectronic applications: recently several devices have been reported that rely on the ultrafast properties of Cd 3 As 2 , the archetypal three-dimensional Dirac semimetal, to make fast photodetectors 23,24 and optical switches. 25 The monopnictide Weyl materials TaAs, TaP, and NbAs also show technological promise due to their sizable, anisotropic nonlinear-optical response.…”
Section: Introductionmentioning
confidence: 99%